Analisa Perbandingan Algoritma Taboo Codes Dan Algoritma Yamamoto’s Recursive Code Untuk Kompresi File Teks Menggunakan Metode Exponential - Arianti Rhamadani (STMIK Budi Darma, 2022)
In the current digital era, the use of data compression technology is very important because the use of data in electronic form is faster to exchange information. Large file sizes require a lot of storage space. Rich text format (rtf) text files have a large size compared to other types of text files with extensions. Because the file size with the extension .rtf is too large, the data transmission process takes a long time. One of the techniques required for this problem is to perform compression. Compression is the process of resizing data to a smaller size. The algorithms used in this study are the Taboo Codes and Yamamoto’s Recursive Code algorithms, each of which has advantages and disadvantages. After the two algorithms are compressed, then a comparison of the two algorithms is carried out using the Exponential method. The exponential comparison method is one of the methods used to determine the priority order of decision alternatives with several criteria. The final result of the comparison process with the exponential method is 7,203, which is Yamamoto’s Recursive Code algorithm. So that the algorithm becomes the fastest and most effective algorithm in compressing text files, this is because the smaller the total value obtained, the less effort is made by the algorithm in compression.